PEMANFAATAN FACEBOOK DALAM KETERAMPILAN MEMPRODUKSI TEKS CERITA SEJARAH PADA SISWA KELAS XII IPS-1 SMA NEGERI 3 BOJONEGORO TAHUN PELAJARAN 2015/2016 - Susanto Susanto (Jurusan Tadris Bahasa Indonesia, 2015)
Facebook already familiar among students, thus giving rise to problems in the form of formulation of the problem. How harness, effectiveness studies, and student learning outcomes associated with social media media (facebook) in improving the learning skills to produce historical narrative text in class XII IPS 1SMAN 3 Bojonegoro academic year 2015/2016? The method in use is the method of data collection in the form of questionnaires and interviews, and observations during the study (good attitude, knowledge and skills). Results of the research in this paper indicate that Facebook utilize media based learning as e-learning will be developed along technology. The learned very look fabulous. Students of class XII IPS -1 amounted to 32 students. Students who scored above 79 to as many as 27 students or equal to 84.4%. This means that students experiencing learning completeness. While students who scored below 79 or 78 down as much as 5 students, equivalent to 15.6%. Means there are five students who did not complete the work TCS.Saran in this study should be a teacher, the use of FB as a learning medium based e-learning, especially in order to improve the achievement of learning outcomes.